Global value chains and the removal of trade protection - Bown, Chad P.; Erbahar, Aksel; Zanardi, Maurizio (European economic review, 2021)
This paper examines how trade protection is affected by changes in the value-added content of production arising through global value chains (GVCs). Exploiting a new set of WTO rules adopted in 1995 that impose an exogenously-timed requirement for countries to re-evaluate their previously-imposed trade protection, we adopt an instrumental variables strategy and identify the causal effect of GVC integration on the likelihood that a trade barrier is removed. Using a newly constructed dataset of protection removal decisions involving 10 countries, 41 trading partners, and 18 industries over 1995–2013, we find that bilateral industry-specific domestic value-added growth in foreign production significantly raises the probability of removing a duty. The results are not limited to imports from China but are only found for the protection decisions of high-income countries. Back-of-the-envelope calculations indicate that rapid GVC growth in the 2000s freed 15% of the trade flows subject to the most common temporary restrictions (i.e. antidumping) applied by high-income countries in 2007.